State-centrism in international relations - Hedžet, Ajda (Teorija in praksa, 2023)
t. This article addresses the deficiency in the area of human rights scholarship in International Relations (IR) by examining the theoretical advancements in IR theory that have led to the emergence of non-state collective actors as a pertinent research topic. It provides a review of the trajectory of the constructivist theoretical approach, which has brought major advancements in how international non-state actors are conceptualised in the human rights IR literature. This considers the limitations and implications of side-lining collective non-state actors within IR theory, arguing that expanding the theoretical understanding of how different collective actors are constituted and attributed with agency can enrich IR human rights scholarship. The article also proposes a potential way forward with respect to non-state collective actors in human rights in IR by identifying a research programme based on practiceoriented approaches to help broaden the ability of scholars to foster interdisciplinary conversations. Expanding along these lines would bridge the existing boundaries within scholarly and disciplinary contexts.
Keywords: collectives; constructivism; Človekove pravice; Država; državocentričnost; human rights; international actors; international relations; konstruktivizem; mednarodni akterji; Mednarodni odnosi; nedržavni akterji; non-state actors; state-centrism